A low-volatile double-crosslinked thermally conductive phase-change gel sheet and preparation method thereof

By adopting dual cross-linking design in thermal phase change materials and introducing high-efficiency thermal fillers and phase change materials, the problems of high volatility and poor stability of traditional thermal phase change materials are solved, and efficient thermal conductivity and low volatility are achieved, which is suitable for the heat dissipation needs of high-performance electronic equipment.

CN118652546BActive Publication Date: 2025-03-14DONGGUAN ZERO THERMAL TREATMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410775497.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-17
Publication Date
2025-03-14
Estimated Expiration
2044-06-17

AI Technical Summary

Technical Problem

The volatile components in traditional thermally conductive phase change materials will gradually evaporate during use, resulting in a decrease in the thermal conductivity of the material and cannot meet the demanding demand for heat dissipation efficiency of high-performance electronic devices.

Method used

Low-volatilization double cross-linked thermal phase change gel sheets are used to form a stable network structure through cross-linking between polyphenylene sulfide and polyimide, and thermally conductive fillers such as alumina composite carbon nanotubes and phase change materials such as lauric acid composite silica gel are introduced.

Benefits of technology

It significantly improves the thermal conductivity and stability of the material, reduces volatility, enhances the safety and environmental protection of use, and can meet the heat dissipation needs of high-performance electronic equipment.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of thermal conductive materials, and specifically discloses a low-volatile double cross-linked thermal conductive phase change gel sheet and a preparation method thereof. The low-volatile double cross-linked thermal conductive phase change gel sheet comprises 10-20 parts of polyphenylene sulfide, 20-30 parts of polyimide, 30-40 parts of thermal conductive filler, 5-15 parts of phase change material and 3-6 parts of cross-linking agent in parts by weight; its preparation method is: polyphenylene sulfide, polyimide, thermal conductive filler, phase change material and cross-linking agent are added to a container and stirred and mixed to obtain a mixture, first heating the mixture to 300-400°C, and extruding it into a desired shape, and cooling it to obtain a low-volatile double cross-linked thermal conductive phase change gel sheet. The low-volatile double cross-linked thermal conductive phase change gel sheet of the present application has the advantages of excellent thermal conductivity and low volatility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of thermal conductive materials, and in particular to a low-volatile double-crosslinked thermal conductive phase change gel sheet and a preparation method thereof. Background Art

[0002] With the rapid development of electronic technology, the performance of electronic equipment has been greatly improved. However, high-performance electronic components will generate a lot of heat during operation. If this heat cannot be dissipated in a timely and effective manner, it will cause the performance of electronic equipment to decline, and even cause equipment failure, and in serious cases, it may cause safety accidents. Therefore, heat dissipation technology has become one of the key technologies to ensure the stable operation of electronic equipment. As an important part of heat dissipation technology, the performance and application of heat dissipation materials are directly related to the heat dissipation effect and operation stability of electronic equipment.

[0003] Thermally conductive phase change materials have been used in the field of electronic equipment heat dissipation for many years. They absorb and release heat through the phase change process, thereby effectively reducing the temperature of electronic components. However, the volatile components in traditional thermally conductive phase change materials will gradually evaporate during use. The loss of volatile components leads to a decrease in the thermal conductivity of the material, making the thermal network incomplete, thereby reducing the thermal conductivity of the material. In addition, the heat generated by high-performance electronic devices during operation is much higher than that of ordinary devices, so they have more stringent requirements for heat dissipation efficiency. Although traditional thermally conductive phase change materials can reduce the temperature of electronic components to a certain extent, they are still insufficient in the heat dissipation of high-power and high-density electronic components.

[0004] Therefore, how to develop a thermally conductive phase change material that has both excellent thermal conductivity and low volatility has become an urgent problem to be solved in this field. Summary of the invention

[0005] In order to solve the above problems, the present application provides a low-volatile double-cross-linked thermally conductive phase change gel sheet and a preparation method thereof.

[0006] The present application provides a low-volatile double-crosslinked thermally conductive phase-change gel sheet. The second aspect of the present application provides a method for preparing the low-volatile double-crosslinked thermally conductive phase-change gel sheet.

[0007] The present application provides a low-volatile double-cross-linked thermally conductive phase-change gel sheet, which adopts the following technical solution:

[0008] A low-volatile double-crosslinked thermally conductive phase-change gel sheet comprises, by weight, 10-20 parts of polyphenylene sulfide, 20-30 parts of polyimide, 30-40 parts of thermally conductive filler, 5-15 parts of phase-change material and 3-6 parts of crosslinking agent.

[0009] Through the above scheme, the gel sheet forms a stable network structure through a double cross-linking design, that is, the cross-linking between polyphenylene sulfide and polyimide. This structure effectively inhibits the volatilization of small molecules, thereby reducing the volatility of the material. Polyphenylene sulfide has excellent high temperature resistance and chemical stability, while polyimide has excellent mechanical properties and wear resistance. The combination of the two enables the gel sheet to maintain stable performance in harsh environments such as high temperature and high pressure.

[0010] Preferably, the thermally conductive filler includes one of aluminum oxide composite carbon nanotubes and boron nitride.

[0011] Through the above scheme, alumina composite carbon nanotubes combine the high thermal conductivity of alumina and carbon nanotubes. Alumina itself has good thermal conductivity, while carbon nanotubes have extremely high thermal conductivity. After the two are compounded, an efficient thermal conductive network can be formed, which significantly improves the thermal conductivity of the gel sheet. Boron nitride is a material with excellent thermal conductivity. Adding it to the gel sheet can significantly improve the overall thermal conductivity efficiency. Due to the high thermal conductivity of these thermally conductive fillers, the gel sheet can transfer heat from the heat source to the heat dissipation device more quickly, thereby optimizing the heat dissipation effect. This is crucial to solving the heat dissipation problem generated during the operation of high-performance electronic equipment.

[0012] Preferably, the preparation method of the alumina composite carbon nanotubes is as follows: 100 parts of carbon nanotubes by weight are sequentially placed in acetone, ethanol and deionized water for ultrasonic cleaning for 5-10 minutes, and then the carbon nanotubes are dried; the carbon nanotubes are placed in 60-80 parts of an acid solution, maintained at 40-50°C, and stirred and acidified at 120-150r / min for 30-60 minutes; the acidified carbon nanotubes are placed in an atomic deposition device, 60-80 parts of a trimethylaluminum solution with a mass concentration of 40-50% are placed, and the temperature in the deposition device is adjusted to 290-310°C, so that the alumina particles generated by the trimethylaluminum solution at high temperature are deposited in the carbon nanotubes to obtain alumina composite carbon nanotubes; the deposited carbon nanotubes are rinsed with deionized water and blown dry with nitrogen.

[0013] Through the above scheme, the carbon nanotubes are placed in an acid solution for stirring and acidification, which can remove the oxides and residual impurities on the surface of the carbon nanotubes, and at the same time activate the surface of the carbon nanotubes, which is conducive to the deposition and bonding of aluminum oxide particles. Using atomic deposition equipment, the aluminum oxide particles produced by trimethylaluminum solution are uniformly deposited in the carbon nanotubes at high temperature. This method can control the particle size and distribution of aluminum oxide particles, achieve a close combination of aluminum oxide and carbon nanotubes, and form stable aluminum oxide composite carbon nanotubes. The aluminum oxide particles are uniformly deposited on the carbon nanotubes to form an efficient thermal conductive network. This composite structure can significantly improve the overall thermal conductivity of the material, making the aluminum oxide composite carbon nanotubes an ideal thermal conductive filler. As a thermal conductive filler, the aluminum oxide composite carbon nanotubes can significantly enhance the thermal conductivity of the gel sheet.

[0014] Preferably, the acid solution is a mixture of a sulfuric acid solution with a mass concentration of 90-95% and a nitric acid solution with a mass concentration of 55-60% in a mass ratio of 1:(2-3).

[0015] Through the above scheme, the mixed use of sulfuric acid and nitric acid can produce a synergistic effect. This mixed acid solution has strong oxidizing and acidic properties. The strong acidity of sulfuric acid can remove the oxide layer and other impurities on the surface of the carbon nanotubes, making the surface of the carbon nanotubes cleaner. The strong oxidizing property of nitric acid helps to form more active sites on the surface of the carbon nanotubes, thereby improving the bonding force between aluminum oxide and carbon nanotubes. The surface of the carbon nanotubes treated with the mixed acid solution is more uniform, which is conducive to the uniform deposition of aluminum oxide particles.

[0016] Preferably, the phase change material comprises lauric acid composite silica gel.

[0017] Preferably, the preparation method of the lauric acid composite silica gel is: 80-100 parts of lauric acid and 20-40 parts of nano-silicon dioxide are mixed by weight, and 50-100 parts of anhydrous ethanol are added and stirred evenly to obtain a mixed solution; 1-5 parts of stearic acid are added to the mixed solution, and stirring is continued, and the temperature is controlled at 5-10°C for 1-2 hours to obtain a gelled mixture; the gelled mixture is placed in a vacuum drying oven for low-temperature drying to remove excess solvent to obtain lauric acid composite silica gel, and the dried lauric acid composite silica gel is ground into powder.

[0018] Through the above scheme, lauric acid has the ability to change its physical state within a specific temperature range. In this process, lauric acid absorbs or releases a large amount of latent heat. This means that it can store thermal energy and release it when needed, thereby playing a role in temperature regulation. Through compounding with nano-silica, the thermal conductivity of lauric acid composite silica gel has been significantly improved. The nano-scale size of nano-silica can fill the gaps between lauric acid molecules, reduce thermal resistance, and make the entire gel material have better thermal conductivity. Lauric acid itself has good thermal stability, and the addition of nano-silica can further improve the thermal stability of the composite gel. This enables lauric acid composite silica gel to maintain stable performance over a wide temperature range and meet the needs of various application scenarios.

[0019] Preferably, the cross-linking agent comprises isocyanate and trichlorobenzene, and the mass ratio of isocyanate to trichlorobenzene is 2:(0.5-1.5).

[0020] In a second aspect, the present application provides a method for preparing a low-volatile double-crosslinked thermally conductive phase-change gel sheet, using the following technical solution:

[0021] A method for preparing a low-volatile double cross-linked thermally conductive phase change gel sheet comprises adding polyphenylene sulfide, polyimide, a thermally conductive filler, a phase change material and a cross-linking agent into a container, stirring and mixing to obtain a mixture, heating the mixture to 300-400°C, extruding the mixture into a desired shape, and cooling the mixture to obtain a low-volatile double cross-linked thermally conductive phase change gel sheet.

[0022] In summary, the present application includes at least one of the following beneficial technical effects:

[0023] 1. The present application adopts polyphenylene sulfide and polyimide to cross-link to form a stable network structure, and introduces thermal conductive fillers and phase change materials. The low-volatile double cross-linked thermal conductive phase change gel sheet prepared not only has excellent thermal conductivity, but also has low volatility, thereby solving the problems of high volatility and poor stability of traditional thermal conductive phase change materials, and improving the safety and environmental protection of the material.

[0024] 2. This application significantly improves the thermal conductivity of the gel sheet by optimizing the composition and preparation process of the thermally conductive filler, especially by using alumina composite carbon nanotubes as the thermally conductive filler, so that it can meet the stringent requirements of high-performance electronic equipment for heat dissipation efficiency.

[0025] 3. This application also provides a detailed method for preparing a low-volatile double-cross-linked thermally conductive phase change gel sheet. The method is simple to operate, easy to control, suitable for large-scale industrial production, and provides strong support for the widespread application of thermally conductive phase change materials. DETAILED DESCRIPTION

[0026] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0027] Preparation Example of Alumina Composite Carbon Nanotubes

[0028] Preparation Example 1

[0029] A method for preparing alumina composite carbon nanotubes:

[0030] 10 kg of carbon nanotubes were placed in acetone, ethanol and deionized water for ultrasonic cleaning for 8 minutes to remove surface impurities, and then the carbon nanotubes were dried.

[0031] The carbon nanotubes were placed in 7 kg of an acid solution, which was a mixture of a 92% sulfuric acid solution and a 58% nitric acid solution in a mass ratio of 1:2.5. The temperature was maintained at 45° C. and the acidification was performed at 135 r / min for 45 minutes to increase the active groups on the surface of the carbon nanotubes.

[0032] The acidified carbon nanotubes are placed in the inner cavity of an atomic deposition furnace, 7 kg of a trimethylaluminum solution with a mass concentration of 45% is added, and the temperature in the atomic deposition furnace is adjusted to 300°C. Under high temperature conditions, the trimethylaluminum decomposes and releases aluminum atoms, which react with oxygen to form aluminum oxide. The aluminum oxide vapor is then transported to the top of the carbon nanotube substrate. Due to the adsorption effect of the carbon nanotube substrate, the aluminum oxide vapor is deposited on the surface of the carbon nanotube to form an aluminum oxide layer, thereby obtaining an aluminum oxide composite carbon nanotube.

[0033] The alumina composite carbon nanotubes were rinsed with deionized water and blown dry with nitrogen to remove residual impurities.

[0034] Preparation Example 2

[0035] A method for preparing aluminum oxide composite carbon nanotubes: The difference from Preparation Example 1 is that the acid solution is a sulfuric acid solution with a mass concentration of 92%.

[0036] Preparation Example 3

[0037] A method for preparing aluminum oxide composite carbon nanotubes: The difference from Preparation Example 1 is that the acid solution is a nitric acid solution with a mass concentration of 58%.

[0038] Preparation Example 4

[0039] A method for preparing aluminum oxide composite carbon nanotubes: The method is different from Preparation Example 1 in that the carbon nanotubes are not treated with an acid solution.

[0040] Preparation example of lauric acid composite silica gel

[0041] Preparation Example 5

[0042] A method for preparing lauric acid composite silica gel:

[0043] 9 kg of lauric acid and 3 kg of nano-silicon dioxide were mixed, and 7.5 kg of anhydrous ethanol was added and stirred evenly to obtain a mixed solution.

[0044] 0.3 kg of stearic acid was added to the mixture, and stirring was continued while controlling the temperature at 8° C. for 1.5 h to allow the mixture to undergo a gelation reaction.

[0045] The gelled mixture was placed in a vacuum drying oven and dried at 50° C. to remove excess solvent, thereby obtaining lauric acid composite silica gel.

[0046] The dried lauric acid composite silica gel is ground into powder so as to be easily mixed with the base material.

[0047] Preparation Example 6

[0048] A method for preparing lauric acid composite silica gel: The difference from Preparation Example 5 is that 7 kg of lauric acid and 5 kg of nano-silicon dioxide are mixed, and 7.5 kg of anhydrous ethanol is added and stirred evenly to obtain a mixed solution.

[0049] Preparation Example 7

[0050] A method for preparing lauric acid composite silica gel: The difference from Preparation Example 5 is that 11 kg of lauric acid and 1 kg of nano-silicon dioxide are mixed, and 7.5 kg of anhydrous ethanol is added and stirred evenly to obtain a mixed solution.

[0051] Example

[0052] Example 1

[0053] Preparation of low-volatile double-crosslinked thermally conductive phase change gel sheet:

[0054] 1.5 kg of polyphenylene sulfide powder with a molecular weight of 15,000, 2.5 kg of polyimide powder with a molecular weight of 28,000, 3.5 kg of alumina composite carbon nanotubes, 1 kg of lauric acid composite silica gel powder and 0.5 kg of a cross-linking agent are added into a clean container. The cross-linking agent contains 0.33 kg of toluene diisocyanate and 0.12 kg of trichlorobenzene. A low-speed agitator at 100 r / min is used to preliminarily mix the materials to ensure that the various materials are initially mixed evenly. Switch to a high-speed stirring mode of 300 r / min and continue to stir the mixture until all materials are fully mixed without obvious particles or lumps.

[0055] The mixture is heated to 350°C and kept warm for 60 minutes. The stirred mixture is added into the hopper of the extruder for extrusion molding. After completion, it is cooled in a vacuum environment to obtain a low-volatile double-cross-linked thermally conductive phase change gel sheet.

[0056] Among them, the alumina composite carbon nanotubes are prepared by Preparation Example 1, and the lauric acid composite silica gel is prepared by Preparation Example 5.

[0057] Example 2

[0058] Preparation of low-volatile double-crosslinked thermally conductive phase-change gel sheet: The difference from Example 1 is that boron nitride is used as the thermally conductive filler.

[0059] Example 3

[0060] Preparation of low-volatile double-crosslinked thermally conductive phase-change gel sheet: The difference from Example 1 is that alumina powder is used as the thermally conductive filler.

[0061] Example 4

[0062] Preparation of low-volatile double-crosslinked thermally conductive phase-change gel sheet: The difference from Example 1 is that carbon nanotubes are used as thermally conductive fillers.

[0063] Example 5

[0064] Preparation of low-volatile double-crosslinked thermally conductive phase-change gel sheet: The difference from Example 1 is that paraffin is used as the phase-change material.

[0065] Example 6

[0066] Preparation of low-volatile double-cross-linked thermally conductive phase-change gel sheet: The difference from Example 1 is that lauric acid is used as the phase-change material.

[0067] Comparative Example

[0068] Comparative Example 1

[0069] Preparation of low-volatile double cross-linked thermally conductive phase change gel sheet: The difference from Example 1 is that 4 kg of polyphenylene sulfide powder with a molecular weight of 15,000, 3.5 kg of alumina composite carbon nanotubes, 1 kg of lauric acid composite silica gel powder and 0.5 kg of a cross-linking agent are added to a clean container.

[0070] Comparative Example 2

[0071] Preparation of low-volatile double cross-linked thermally conductive phase change gel sheet: The difference from Example 1 is that 4 kg of polyimide powder with a molecular weight of 28,000, 3.5 kg of alumina composite carbon nanotubes, 1 kg of lauric acid composite silica gel powder and 0.5 kg of cross-linking agent are added to a clean container.

[0072] Comparative Example 3

[0073] Preparation of low-volatile double-crosslinked thermally conductive phase-change gel sheet: The difference from Example 1 is that the alumina composite carbon nanotubes are prepared by Preparation Example 2.

[0074] Comparative Example 4

[0075] Preparation of low-volatile double-crosslinked thermally conductive phase-change gel sheet: The difference from Example 1 is that the alumina composite carbon nanotubes are prepared by Preparation Example 3.

[0076] Comparative Example 5

[0077] Preparation of low-volatile double-crosslinked thermally conductive phase-change gel sheet: The difference from Example 1 is that the alumina composite carbon nanotubes are prepared by Preparation Example 4.

[0078] Comparative Example 6

[0079] Preparation of low-volatile double-cross-linked thermally conductive phase-change gel sheet: The difference from Example 1 is that the lauric acid composite silica gel is prepared by Preparation Example 5.

[0080] Comparative Example 7

[0081] Preparation of low-volatile double-cross-linked thermally conductive phase-change gel sheet: The difference from Example 1 is that the lauric acid composite silica gel is prepared by Preparation Example 6.

[0082] Performance testing

[0083] Detection Methods

[0084] The thermal conductive phase change gel was made into a disc with a diameter of 12 mm and a thickness of 2 mm. The sample surface was ensured to be flat, free of bubbles and cracks. The sample was placed on the sample stage of the laser flash method test equipment to ensure good contact between the sample and the equipment. The test was performed at room temperature of 20°C with a frequency of 100 Hz and 20 J / pulse.

[0085] The laser pulse is irradiated onto one surface of the sample. The laser pulse heats the sample for 5 seconds, causing the surface temperature of the sample to rise rapidly. At the same time, the device records the temperature change process on the other side of the sample. According to the heat diffusion equation and Fourier's heat conduction law, the thermal conductivity of the sample is calculated by calculating the half-heating time.

[0086] The thermal conductive phase change gel was made into a disc with a diameter of 12 mm and a thickness of 2 mm. The weight of the disc was measured. The disc was tightly attached to a flat heat source and placed at a constant temperature of 150°C for 7 days. The weight of the disc was remeasured and the weight loss rate was calculated.

[0087] Table 1 Data statistics

[0088] Thermal conductivity W / (m·K) Weight loss rate / % Example 1 7.85 0.48 Example 2 6.48 0.55 Example 3 4.10 0.75 Example 4 5.32 0.67 Example 5 6.15 0.88 Example 6 6.32 0.73 Comparative Example 1 7.75 1.05 Comparative Example 2 7.73 1.17 Comparative Example 3 5.98 0.63 Comparative Example 4 6.23 0.58 Comparative Example 5 5.56 0.65 Comparative Example 6 6.63 0.61 Comparative Example 7 5.78 0.53

[0089] Combining Example 1 and Comparative Examples 1-2 with Table 1, it can be seen that a stable network structure is formed after the polyphenylene sulfide powder and polyimide are double cross-linked as a substrate. This structure effectively inhibits the volatilization of small molecules, thereby reducing the volatility of the material.

[0090] It can be seen from Example 1 and Comparative Examples 3-5 and Table 1 that the mixed use of sulfuric acid and nitric acid can produce a synergistic effect. This mixed acid solution has strong oxidizing properties and acidity. The strong acidity of sulfuric acid can remove the oxide layer and other impurities on the surface of the carbon nanotubes, making the surface of the carbon nanotubes cleaner. The strong oxidizing property of nitric acid helps to form more active sites on the surface of the carbon nanotubes, thereby improving the binding force between aluminum oxide and carbon nanotubes. The surface of the carbon nanotubes treated with the mixed acid solution is more uniform, which is conducive to the uniform deposition of aluminum oxide particles. Compared with using one acid alone, the effect is better.

[0091] Combining Example 1 and Comparative Examples 6-7 with Table 1, it can be seen that the thermal conductivity of the lauric acid composite silica gel is significantly improved by compounding with nano-silicon dioxide. The nano-scale size of nano-silicon dioxide can fill the gaps between lauric acid molecules, reduce thermal resistance, and make the entire gel material have better thermal conductivity. Lauric acid itself has good thermal stability, and the addition of nano-silicon dioxide can further improve the thermal stability of the composite gel.

[0092] Combining Examples 1-6 and Table 1, it can be seen that the use of alumina composite carbon nanotubes as thermal conductive fillers has the best effect, and the use of lauric acid composite silica gel as the phase change material to obtain a thermal conductive phase change gel sheet has better performance than conventional options.

[0093] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A low-volatile double-cross-linked thermally conductive phase change gel sheet, characterized in that: The raw materials include 10-20 parts of polyphenylene sulfide, 20-30 parts of polyimide, 30-40 parts of thermal conductive filler, 5-15 parts of phase change material and 3-6 parts of cross-linking agent in parts by weight; the thermal conductive filler includes one of aluminum oxide composite carbon nanotubes and boron nitride, and the preparation method of the aluminum oxide composite carbon nanotubes is as follows: 100 parts by weight of carbon nanotubes were sequentially placed in acetone, ethanol and deionized water for ultrasonic cleaning for 5-10 minutes, and then the carbon nanotubes were dried; Place the carbon nanotubes in 60-80 parts of an acid solution, maintain the temperature at 40-50°C, and stir at 120-150 r / min for 30-60 minutes; The acidified carbon nanotubes are placed in an atomic deposition device, 60-80 parts of a trimethylaluminum solution with a mass concentration of 40-50% are added, and the temperature in the deposition device is adjusted to 290-310° C., so that the aluminum oxide particles generated by the trimethylaluminum solution at high temperature are deposited in the carbon nanotubes to obtain aluminum oxide composite carbon nanotubes; The deposited carbon nanotubes were rinsed with deionized water and dried with nitrogen gas; The acid solution is a mixture of a sulfuric acid solution with a mass concentration of 90-95% and a nitric acid solution with a mass concentration of 55-60% in a mass ratio of 1:(2-3); The phase change material includes lauric acid composite silica gel; The preparation method of the lauric acid composite silica gel is as follows: Mix 80-100 parts of lauric acid and 20-40 parts of nano-silicon dioxide, and add 50-100 parts of anhydrous ethanol and stir evenly to obtain a mixed solution; Add 1-5 parts of stearic acid to the mixture, continue stirring, and control the temperature at 5-10°C for 1-2 hours to obtain a gelled mixture; The gelled mixture is placed in a vacuum drying oven for low temperature drying to remove excess solvent to obtain lauric acid composite silica gel, and the dried lauric acid composite silica gel is ground into powder; The cross-linking agent comprises isocyanate and trichlorobenzene, and the mass ratio of the isocyanate to the trichlorobenzene is 2:(0.5-1.5).

2. A method for preparing the low-volatile double-crosslinked thermally conductive phase change gel sheet as claimed in claim 1, characterized in that: Add polyphenylene sulfide, polyimide, thermal conductive filler, phase change material and cross-linking agent into a container and stir to obtain a mixture. First, heat the mixture to 300-400°C and extrude it into a desired shape. After cooling, a low-volatile double cross-linked thermal conductive phase change gel sheet is obtained.

Citation Information

Patent Citations

  • Polyimide resin composition

    EP0294129A1

  • Polyalloy of polyphenylene sulfide and polyimide

    US4017555A